Evaluation of classroom teaching by students and peers for many purposes in academia - El-Sabban, Farouk (Faculty of Medicine, University of Malaya, 2001)
Improving upon the quality of teaching staff at all educational institutions is a very significant objective. Evaluation of teaching performed by individuals at such institutions would be instrumental in assessing the quality of such teaching and a tool towards its improvement. In this article, one scheme for teaching evaluation by students and another by peers are proposed and discussed. Assessment by students may provide contrasting results to those obtained from peers. For a "just and fair" overall assessment of one's teaching, it is recommended that students' evaluation would be combined with those of peers. Results of such an evaluation of teaching should be perceived as being valuable in providing feedback to the teacher and can be utilized for many purposes by academicians and administrators.